Household awareness, acceptance, and willingness to pay for renewable energy - Leomar Sabroso; Maria Niña Kyla Suaner; Elaine Lucmayon; John Roland Asio (Diversitas Journal, 2024)
The purpose of this study was to determine the level of household awareness, acceptance, and willingness to pay for renewable energy. It is quantitative research that determines the significant difference specifically in the amount of willingness to pay for renewable energy when analyzed according to profile; the significant relationship precisely between the level of awareness and willingness to pay; and the significant relationship particularly between the level of technology acceptance and willingness to pay. The study's independent variables are the level of awareness and the technology acceptance model. The dependent variable is the willingness to pay. The mediator variable is the respondents’ profile. Respondents were contacted through online platforms for data gathering and given an online survey questionnaire. Once they were done with the profile section, they sought to answer questions prior to their level of awareness, technology acceptance method, and willingness to pay. Next, the results were statistically analyzed using Logistic Regression and Two-Way ANOVA. After running the data, it is interpreted to determine the significant difference and relationship. The researchers then determined that there is a significant difference in the amount of willingness to pay for renewable energy when analyzed according to profile; a significant relationship between the level of awareness and willingness to pay; and a significant relationship between the level of technology acceptance method, specifically the perceived usefulness, and willingness to pay.